(untitled) (Research, Society and Development, 2019)
The present research addresses the importance of teacher training for professionals in the technical areas, especially those of Fashion Design. The purpose of this study is to reflect on the importance of the teacher training of the Fashion teacher, considering that there is a shortage of training courses and qualification in the area of teaching. The research carried out is of the qualitative bibliographical type. The data collection was carried out in articles, books and on the websites of three private universities located in the state of Rio Grande do Sul. The research was carried out in the months of June and July of 2018. It can be concluded that the Fashion area is new in Brazil, and higher education courses with a degree in Fashion, are still seeking their consolidation in society and in the educational environment. It should be pointed out that the main courses in this area have as main purpose in their curricular curriculum to approach technical and also theoretical disciplines, so that trained professionals can enter the job market qualified for acting in the area of education.